Big Qual A Guide to Breadth-and-Depth Analysis - Weller, Susie; Davidson, Emma.; Edwards, Rosalind; Jamieson, Lynn. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"...The ultimate guide for learning how to do big qualitative research. The rapidly expanding world of big data calls for new solutions to manage and analyse large volumes of qualitative data now becoming available to social scientists everywhere...Big Qual will lead you on a rewarding quest to navigate qualitative data landscapes." - Kathy A. Mills, Australian Catholic University, Australia "The volume takes a unique approach to analysis ... and can be used as a methodological treatise grounded in empirical research, or the individual chapters as discrete modules in specific aspects of analysis." - Malcolm Williams, Cardiff University, UK "This approach offers readers a way to think about how to analyse big qualitative data in meaningful and theoretically grounded ways. Weller et al.'s book will serve as an important guidepost as we increasingly encounter and work with big qualitative datasets." - Jessica Nina Lester, Professor of Qualitative Methodology, Indiana University Bloomington, USA This upper-level textbook presents a new approach to large scale qualitative analysis - the pioneering breadth-and-depth method. It covers the strengths and deployment of "big qual" as a distinct research methodology. The book will appeal to students and researchers across disciplines and methodological backgrounds. The growing availability of large qualitative data sets presents exciting opportunities. Pooling multiple qualitative data sets enhances the possibility of theoretical generalisability and strengthens claims from qualitative research about understanding how social processes work. Given the evolving possibilities that big data offers the humanities and social sciences, this book will be a must-have resource, building capacity and provoking new ways of thinking about qualitative research and its analysis. Susie Weller is Senior Research Fellow in the Clinical Ethics, Law and Society (CELS) research group and a Fellow of the Centre for Personalised Medicine, University of Oxford, UK. Emma Davidson is Lecturer in Social Policy and Qualitative Research Methods at the University of Edinburgh, UK and Co-Director at the Centre for Research on Families and Relationships, Scotland. Rosalind Edwards is Professor of Sociology and a Fellow of the National Centre for Research Methods at the University of Southampton, UK. Lynn Jamieson is Professor of the Sociology of Families and Relationships at the University of Edinburgh, UK and Co-Director at the Centre for Research on Families and Relationships, Scotland. .
PART I: FROM BIG QUAL TO THE BREADTH-AND-DEPTH METHOD -- 1. The place and value of large-scale qualitative data analysis -- 2. Introducing the breadth-and-depth method -- PART II: AN ENQUIRY-LED OVERVIEW OF QUALITATIVE RESEARCH DATA SETS -- 3. Sourcing and searching for suitable data sets -- 4. 'Ariel surveying': Overviewing the data and constructing a corpus -- PART III: MOVING BETWEEN BREADTH-AND-DEPTH IN QUALITATIVE ANALYSIS -- 5. 'Geophysical surveying': Recursive surface 'thematic' mapping using data mining tools -- 6. 'Test pit sampling': Preliminary analysis -- 7. 'Deep excavations': In-depth interpretive analysis -- PART IV: REFLECTING ON THE IMPLICATIONS OF LARGE-SCALE QUALITATIVE ANALYSIS -- 8. Ethics and practice -- 9. Big qual and the future of qualitative analysis.
Keywords: Sociology -- Methodology; Quantitative research; Sampling (Statistics).; Sociological Methods; Data Analysis and Big Data; Methodology of Data Collection and Processing